Digital art: when artistic and cultural muse merges with computer technology - Marcos, Adérito (2011)
Digital technologies have become ostensibly ubiquitous and highly expressive over the last 15 years. Today, more people are exploring innovations in information and communications technology in global communication networks, as well as in media tools, to create new aesthetical representational forms of information. In this article, the author discusses and analyzes the concepts and definitions behind digital art and the technological issues related to artistic and cultural heritage applications.